Incidence and prevalence of musculoskeletal disorders work related. A Systematic Review - José Castela Costa (2013)
Musculoskeletal disorders are one of the most common work-related disease. Nevertheless, sometimes, even for an expert, is very difficult to establish the relationship between work and sickness by the huge number of variables that may influence the outcome of these diagnoses. By these reasons, the authors aim to present a systematic review of prevalence and incidence of MSD related with occupational risk factors. Only a few studies were found with comparable approaches and that are considered by the authors adequate to prove this relation. More studies are needed to clarify the relation between work and WRMSD's, especially prospective investigations, ranging from broad economic sectors and work activities, with similar methodologies.